2021
DOI: 10.1021/acsaem.1c02897
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene): A New Binder for Conventional and Printable Lithium-Ion Batteries

Abstract: The growing interest in printable batteries leads to the necessity of developing new and more efficient materials that meet the required processability and performance characteristics. In this work, a poly­(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P­(VDF-TrFE-CFE)) terpolymer has been used for the first time as a polymer binder for lithium-ion battery cathodes and their electrochemical characteristics have been compared with cathodes prepared with the commonly used poly­(vinylidene fluoride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…98 Considering its properties, this ter-polymer has been also used as a polymer binder for electrodes in Li-ion batteries devices. 99 In the future, it is expected to find application in other high-tech areas.…”
Section: Processabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…98 Considering its properties, this ter-polymer has been also used as a polymer binder for electrodes in Li-ion batteries devices. 99 In the future, it is expected to find application in other high-tech areas.…”
Section: Processabilitymentioning
confidence: 99%
“…439 Poly(VDF-ter-TrFE-ter-CFE) ter-polymer has been also used as a polymer binder for cathode printed electrodes by DIW, showing suitable rate battery performance, as shown in Figure 29e. 99 In fact, different PVDF copolymers have been also evaluated for Li-sulfur battery development (Figure 29f), 440 poly(VDF-co-TrFE) showing improved performance with respect to PVDF and poly(VDF-co-CTFE) due to the strong chemical interaction with polysulfides based on its high molecular polarity. 440 The influence of PVDF binders on the porosity of composite electrodes for lithium-sulfur (Li-S) batteries was also addressed, the highest battery performance being observed for poly(VDF-co-HFP).…”
Section: Energy Storage Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed by active materials, fillers (organic as graphene oxide [GO] or inorganic as ceramic materials), and sometimes a polymer matrix (poly vinylidene fluoride [PVDF] mostly). Joao et al 79 reported a terpolymer (which results from copolymeration of three monomers) called poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) suitable for LDM processing to be used as a polymer binder for LIB. The terpolymer possess the needed rheological properties to be printed by LDM and it showed enhanced dielectric constant and low electric loss compared to the PVDF (one of the most common polymer binders in the current commercial batteries).…”
Section: Liquid Deposition Modelingmentioning
confidence: 99%
“…37 Poly(vinylidene uoride) P(VDF) and its related copolymers with triuoroethylene P(VDF-TrFE) exhibit excellent chemical resistance, thermal stability, and high organic selectivity, as well as good mechanical and membrane-forming properties which allow applications like ultraltration, microltration and pervaporation membrane manufacturing processes. [38][39][40] P(VDF) hollow ber membranes were used for preparation of catalytic membranes by in situ reduction of nickel salt with sodium borohydride (NaBH 4 ) for hydrogen production. 41 Many studies have been focusing on introducing isodimensional nanostructured materials such as graphene oxide, TiO 2 , SiO 2 , Al 2 O 3 and ZnO into modied P(VDF) and P(VDF-TrFE) to produce membranes with enhanced anti-pollution, hydrophilic or piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%